Knowledge, attitudes and good practices concerning SARS-CoV-2 infection and vaccines among Italian nursing students: a cross-sectional study - Maurici, Massimo; Simonelli , Ilaria; Roncari, Matteo; Ungaro, Stefano; Mazzotta, Rocco; Gentile , Lavinia; Zeffiro, Valentina; Pancaldi, Alessandra; Alvaro, Rosaria; Bulfone, Giampiera (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: During the Covid-19 pandemic, the world implemented strategies to contain and prevent the transmission of SARS-CoV-2. Nurses played a key role in informing and educating the population on correct health management and the fight against SARS-CoV-2 infection. This study aims to analyse Italian nursing students’ knowledge, attitudes and good practices concerning SARS-CoV-2 infection and vaccines. Methods: A cross-sectional study was conducted. A convenience sample of nursing students from a nursing-degree programme of University of Rome Tor Vergata was considered. The Knowledge, Attitudes and Good Practices concerning SARS-CoV-2 among Nursing Students (KAGP-COV-Ns) questionnaire was used. Results: A convenience sample of 303 nursing students enrolled in a three-year degree program was considered. Of the participants, 74.6% were female, with a mean age of 23.86 years (standard deviation 5.41). The participants demonstrated good knowledge of the SARS-CoV-2 virus, its risk factors, and associated symptoms. However, they exhibited inadequate knowledge regarding the incubation time of SARS-CoV-2, the gold-standard test, and treatment options. In our study, first- and third-year students differed in terms of knowledge and good practices, with the latter performing better on the questionnaire. Overall, participants displayed positive attitudes towards SARS-CoV-2 infection but showed a lower positive attitude towards providing information to citizens and becoming nurse vaccinators. Conclusions: Our study revealed that a subset of students exhibited vaccine hesitancy. A deeper understanding of this phenomenon would be very valuable for planning future strategies to promote adherence to preventive practices related to Covid-19 or other pandemics.